Fuel consumption of road commercial vehicles in the driving schedule - Canale, Antonio C.; Navarro, Helio A. [UNESP]; Saraiva, José R.; Vastas, Nicolas B.; D'Elboux, José Eduardo (SAE International, 1997)
The fuel consumption is an important factor in the vehicle development due the fact that it has a direct effect on its trade aims. Besides that, it is known that the petrol is a scarce fuel. In this paper it is presented a procedure of fuel consumption calculation for a vehicle traveling in driving schedule. In such calculation it has been taken into account the operational conditions (load, pavement, climbing road, among others) and the building characteristics (map engine, transmission, frontal area, tire, among others) of road vehicles. There has also been an application of the theoretical model developed in a sample Mercedes-Benz do Brasil vehicle which has been compared with the values of experimental tests. Copyright © 1997 Society of Automotive Engineers, Inc.
Keywords: Building characteristics; Consumption calculation; Experimental test; Frontal areas; Mercedes Benz; Operational conditions; Road vehicles; Theoretical models; Vehicle development; Automobiles; Roads and streets; Vehicles; Vehicle transmissions